Mobile Application Development Analysis for Cafe Reservations and Delivery Order - Anggy Trisnadoli; Rika Perdana Sari; Iqbal Setiawan (Department of Informatics, Universitas Islam Negeri Syarif Hidayatullah, 2023)
Owning a cafe is one of a business that is currently trending in Indonesia, especially in Pekanbaru. With a wide range of cafes in Indonesia, it is directly proportional to the competition among the owners of a cafe. With the rapid development of technology, each cafe owner innovates a delivery order feature to compete with their competitors. They believe it will be a channel for business marketing to be efficient, fast, and sophisticated by providing delivery order features. The delivery order feature provides in two ways; call center by telephone and through an Android-based delivery order application offered by motorcycle taxi online. However, the weakness of using delivery orders through a mobile application is that there is an additional charge due to service fees and expensive shipping costs, which are burdensome to the customers. Regarding this, not having enough space also becomes a primary problem. For that matter, developing an Android application can make the customers easier to order food and drink online. In addition, customers can make reservations and order food or drinks simultaneously, which minimizes customers from running out of space.